Design a novel SSSC based FOPID controller for the hybrid PV-DFIG-based system to enhance transient stability and dampen power oscillations - Ramalingegowda, Chethan Hiremarali; Rudramoorthy, Mageshvaran; Mahesh Kumar, K. M. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The integration of photovoltaic (PV) and wind energy systems is becoming in creasingly significant in the modern energy sector. Among various technologies, doubly fed induction generator (DFIG)-based wind power systems are extensively utilized due to their superior power control capabilities. Conventional control strategies, such as proportional-integral (PI) controllers, are commonly implemented to stabilize system waveforms. However, recent advancements highlight the potential for improved oscillation damping through optimized controller designs. This paper introduces an optimal fractional-order proportional integral-derivative (FOPID) controller integrated with a static synchronous series compensator (SSSC) to enhance power system stability. The proposed approach incorporates the dynamic characteristics of a wind energy conversion system (WECS) connected to an infinite grid. A detailed WECS model is developed to assess the effectiveness and robustness of the proposed controller in mitigating power oscillations, particularly under varying wind conditions. The proposed FOPID controller offers enhanced flexibility for parameter tuning, enabling precise damping of power oscillations, and presents a significant advancement over traditional wind turbine systems based on permanent magnet synchronous machines (PMSM).